Mechanism of Bazhen decoction in the treatment of colorectal cancer based on network pharmacology, molecular docking, and experimental validation - Lu, Shuai; Sun, Xibo; Zhou, Zhongbao; Tang, Huazhen; Xiao, Ruixue; Lv, Qingchen; Wang, Bing; Qu, Jinxiu; Yu, Jinxuan; Sun, Fang; Deng, Zhuoya; Tian, Yuying; et al. (Frontiers in Immunology, 2023)
Objective: This study aims to explore the core components, key targets, and potential mechanisms of BZD treatment for CRC. TCMSP was employed to acquire the BZD's active ingredient and targets. Meanwhile, the Drugbank, TTD, DisGeNET, and GeneCards databases were used to retrieve pertinent targets for CRC. Cytoscape software was used to construct an "herb-ingredient-target" network and identify core targets. GO and KEGG pathway enrichment analyses were conducted using R language software. Molecular docking of key ingredients and core targets of drugs was accomplished using PyMol and Autodock Vina software .Cell and animal research confirmed BZD efficacy and mechanism in treating colorectal cancer. Results: The intersection of BZD and CRC yielded 98 targets, which were utilized to construct the "herb-ingredient-target" network. The four key effector components with the most targets were quercetin, kaempferol, licochalcone A, and naringenin. PPI analysis revealed that the core targets of BZD in treating CRC were AKT1, MYC, CASP3, ESR1, EGFR, HIF-1A, VEGFR, JUN, INS, and STAT3. The GO and KEGG enrichment analysis demonstrates that BZD can modulate multiple signaling pathways related to CRC, like the T cell receptor, PI3K-Akt, apoptosis, P53, and VEGF signaling pathway. In vitro, studies have shown that BZD inhibits CRC cell growth and invasion and promotes apoptosis. Animal experiments have shown that BZD treatment can reverse abnormal expression of PI3K, AKT, MYC, EGFR, HIF-1A, VEGFR, JUN, STAT3, CASP3, and TP53 genes.BZD also increases the ratio of CD4 + T cells to CD8 + T cells in the spleen and tumor tissues, boosting IFN-γ expression, essential for anti-tumor immunity. Furthermore, BZD has the potential to downregulate the PD-1 expression on T cell surfaces, indicating its ability to effectively restore T cell function by inhibiting immune checkpoints. Conclusions: BZD can reverse the abnormal expression of genes such as PI3K, AKT, MYC, EGFR, HIF-1A, VEGFR, JUN, STAT3, CASP3, and TP53, and suppresses the progression of colorectal cancer by regulating signaling pathways such as PI3K-AKT, P53, and VEGF. Furthermore, BZD can increase the number of T cells and promote T cell activation in tumor-bearing mice, enhancing the immune function against colorectal cancer.